PENGARUH LIMBAH CANGKANG KELAPA SAWIT TERHADAP KUAT TEKAN DAN BERAT BETON - Raja Marpaung; Lina Flaviana Tilik (Politeknik Negeri Sriwijaya, 2012)
Concrete as a building material favored by many experts in the field of structure, because it is easily formed, prepared and executed, and mixtures of materials are easy to obtain. However, conventional concrete still shows many weaknesses, including structure components which is relatively heavy, and relatively not too high in strength (when compared to steel). For that reason, research and innovation of materials are required to obtain a concrete mixture able to produce concrete that is lightweight but high strength. Material innovation is done by using lightweight aggregate as coarse aggregate substitute in the form of oil palm shell waste which still untapped by industries This was chosen as the waste oil palm shells as aggregate qualify mild violence and have a good and not easily damaged in the concrete.The study was conducted to determine and compare the value of compressive strength, tensile strength and heavy volume concrete produced from a mixture of concrete with substitution of oil palm shells with coarse aggregate with a variation of 10%, 20%, 30%, 40% and 50%. Quality concrete planned in this study is K-250.The test result shows that the oil palm shell concrete mixed, results compressive strength, tensile strength of concrete is lower and lighter weight concrete, the more the percentage of oil palm shells is substituted with coarse aggregate, the more decline the compressive strength, tensile strength of concrete will be, but weight concrete is also lighter. Percentage reduction in compressive strength of the smallest obtained in a mixture of oil palm shell concrete + 28 days is 29.31% - 69.39%., The decrease percentage in tensile strength is obtained in a mixture of oil palm shell concrete age of 28 days which is 30.55 % - 99.66%., and the percentage reduction of weight concrete mixture obtained in most large oil palm shell concrete + 28 days is 1.70% - 23.03 %.The biggest ratio of ft / fc is obtained on OPS concrete mixture of 28 days which is 11.69% in the variation OPS 10%, whereas in the OPS mixture of 40% and 50% ratio ft / fc' is very small.